Potent anti-diabetic effects of MHY908, a newly synthesized PPAR α/γ dual agonist in db/db mice. - Min Hi Park (Public Library of Science (PLoS), 2013)
Peroxisome proliferator-activated receptor (PPAR) α/γ dual agonists have been developed to alleviate metabolic disorders and have the potential to be used as therapeutic agents for the treatment of type 2 diabetes. In this study, we investigated the effects of a newly synthesized PPAR α/γ dual agonist, 2-[4-(5-chlorobenzo [d] thiazol-2-yl) phenoxy]-2-methylpropanoic acid (MHY908) on type 2 diabetes in vitro and in vivo. To obtain initial evidence that MHY908 acts as a PPAR α/γ dual agonist, ChIP and reporter gene assays were conducted in AC2F rat liver cells, and to investigate the anti-diabetic effects and molecular mechanisms, eight-week-old, male db/db mice were allowed to eat ad libitum, placed on calorie restriction, or administered MHY908 (1 mg or 3 mg/kg/day) mixed in food for 4 weeks. Age-matched male db/m lean mice served as non-diabetic controls. It was found that MHY908 enhanced the binding and transcriptional activity of PPAR α and γ in AC2F cells, and it reduced serum glucose, triglyceride, and insulin levels, however increased adiponectin levels without body weight gain. In addition, MHY908 significantly improved hepatic steatosis by enhancing CPT-1 levels. Remarkably, MHY908 reduced endoplasmic reticulum (ER) stress and c-Jun N-terminal kinase (JNK) activation in the livers of db/db mice, and subsequently reduced insulin resistance. The study shows MHY908 has beneficial effects on type 2 diabetes by simultaneously activating PPAR α/γ and improving ER stress, and suggests that MHY908 could have a potent anti-diabetic effect as a PPAR α/γ dual agonist, and potential for the treatment of type 2 diabetes.